Phenomenological Study and The Effect of Human Resources Capability and The Implementation of Performance-Based Budgeting (PBB) Model on Institution Performance - Supriyadi, Imam; Nurhayati, Immas; Tanjung, Hendri (Jurnal Manajemen, 2024)
The purpose of this study was to analyze the phenomenological study and the effect of human resources capability and the implementation of performance based budgeting (PBB) on institution performance. This study uses mix method. The results of deep interview can concluded that the implementation of PBB at University of Ibn Khaldun Bogor had been carried out but haven’t maximal yet in implementation. The relationship between the human resources capability and the implementation of PBB with institution performance will be tested using multiple linear regression analysis. The independent variables are the human resources capability and the implementation of PBB and the dependent variable is institution performance. The relationship between variabels can be written: Y = 0,467+ 0,183 X1 + 0,798X2. Based on a multiple regression test, only the implementation of performance based budgeting variables have a significant effect on institution performance. The F test showed that all variables can explain the dependent variables. The coefficient of determination of 75,4% means human resources capability and the implementation of performance based budgeting affect institution performance by 75,4%, and the remaining 24,6% is influenced by other factors that are not described in this study.